Evaluating the Long-Term Efficacy of Acupuncture Therapy for Subacute Poststroke Aphasia: Study Protocol for a Randomized, Blinded, Controlled, Multicentre Trial. (12th February 2021) - Li, Xiaolin; Gao, Ying; Zhang, Chi; Zhang, Qingsu; Xin, Xiyan; Tan, Zhongjian; Zhang, Binlong; Fan, Ruiwen; Huang, Xing; Xu, Minjie; Shu, Xin; Yan, Heming; et al.
Abstract : Background . Poststroke aphasia (PSA) is a disabling condition that decreases the quality of life, and the duration of the disease harms the quality of life of PSA patients. Acupuncture has been widely employed for PSA. There is some evidence for the immediate treatment efficacy of acupuncture for PSA; however, long-term results after acupuncture may be poorer. Methods . This is a multicentre, randomized, blinded, nonacupoint (NA) acupuncture controlled, multimodal neuroimaging clinical trial. A total of 48 subjects with subacute PSA will be randomly assigned to an acupoint group or an NA control group. The acupoint group will receive acupuncture with normal needling at DU20, EX-HN1, HT5, GB39, EX-HN12, EX-HN13, and CV23. The NA control group will receive acupuncture in locations not corresponding to acupuncture points as sham acupoints. Both groups will receive identical speech and language therapy thrice a week for four weeks. The primary outcome will be the change in the aphasia quotient (AQ) score measured by the Western Aphasia Battery (WAB) test during the 12th week after randomization. Participants will be blindly assessed at prerandomization (baseline) and 4 weeks, 12 weeks, and 24 weeks after randomization. The secondary outcomes include the Boston Diagnostic Aphasia Examination (BDAE) score, the Disease Prognosis Scale score for ischaemic stroke, etc. Magnetic resonance imaging (MRI) and electroencephalogram (EEG) will also be performed at 4-time intervals as secondary outcomes. All scores and image evaluations will be taken at the same point as the linguistic evaluation. The multilevel evaluation technique will be used to assess the long-term efficacy of acupuncture therapy. MRI scans and EEG will be used to assess acupuncture-related neuroplasticity changes. Discussion . The results from our trial will help to supply evidence for the long-term acupuncture effects for PSA over a long follow-up period. It will provide valuable information for future studies in the field of PSA treatment. The trial was registered at the Chinese Clinical Trial Registry on 16 March 2020 (ChiCTR2000030879 ).